Selection of new clones of linalool chemotype from genetic recombination in Lippia alba - Elcio Rodrigo Rufino (Bragantia, 2012)
The aromatic and medicinal species Lippia alba is vigorous and rugged native to the South America (Atlantic Rainforest). Because it is an allogamous and self-incompatible species, natural populations have high morphological and chemical variability. This work had as objective to conduct a preliminary screening to identify new promising clones from a novel (recombinant) base population of Lippia alba with regard to its agronomic and phytochemical traits, using the linalool oil or chemotype as model. The two superior linalool clones, obtained by collection, were used as controls. Traits evaluated included: dry mass of leaves (DML), oil yield percentage (EOY%), oil production per plant (OP), and linalool percentage (LN%). Forty linalool chemotype clones were evaluated in three experiments, in a random block design with four replicates and four cuttings (clones) per plot. Besides means comparisons, multivariate analysis was used in order to aid in the preliminary selection of clones. There were positive correlations from moderate to strong for DML vs. EOY%, OP vs. EOY% and DML vs. OP. Linalool clones superior or similar to both controls were identified for the DML, EOY%, OP, and LN% traits (univariate analyses), aimed at further validating experimentation. Five distinct groups were defined in the cluster analysis (UPGMA), each containing subgroups as well.